(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
In a fast-paced world where financial inducement is being normalised, journalism professional code of ethics hinged on objectivity, accuracy, fairness, balance and truth became necessary to guide journalists against unprofessional conduct. Despite, scholarly perspectives suggest a decline in news credibility due to news commercialisation. Thus, the sanctity of news is gradually being infiltrated as published or broadcast news promote the interests of the elites, government and private organisations. The foregoing constitutes the challenge. This study, therefore gauged perceptions of journalists of news commercialisation as a recurring ethical question in the Nigerian mediasphere. The researchers relied on survey research design using questionnaire as instrument of data collection with the sample comprised of journalists who are registered members of the Nigerian Union of Journalists (NUJ). The sample of size of 269 was determined with the use of Cochran formula from 5945 being the population of members of the NUJ.The study recorded a 95 percent response rate with 256 responses. Findings revealed that news commercialisation remain unabated in the industry as it is mainly about the need for financial gains in order to keep the medium afloat. Motivated by this consideration, journalists sacrifice the principles of fairness, objectivity, independence at the altar of pecuniary gain for their organisation. The practice poses great threat to individuals and communities often neglected in pursuit of financial gains just as much as the watchdog role of the media is diminished in the process. The researchers concluded that news commercialisation creates an imbalance in news space and airtime allocation as attention is focused on financial gains. Therefore, it was recommended that the media balances the news allocation and ensure that the public interest is protected.